Applying the ltcc-technology to obtain hexaferrites for base layers of microstrip shf devices - Chitanov, Denis; Kostishyn, Vladimir; Kozhitov, Lev; Adamtsov, Artem (Eastern-European Journal of Enterprise Technologies, 2016)
By the method of low-temperature co-fired ceramics (LTCC), with the addition of a small amount of reaction glasses with the composition Bi2O3–B2O3–SiO2–ZnO (BBSZ), we obtained the samples of isotropic and anisotropic polycrystalline hexaferrites BaFe12O19 and SrFe12O19 for the base layers of the subminiature microstrip ferrite untying instruments of the short–wave part of the millimeter wavelength ranges. The LTCC-technology makes it possible to simultaneously achieve compaction of the samples below 900 °C using the process of sintering of hexaferrites with the addition of a small amount of reaction glasses, which are based on Bi–B–Zn–Si–О (BBSZ). It was established that the use in the LTCC-technology of operation of pressing the samples (tablets) in the magnetic field makes it possible to obtain anisotropic hexaferrites, pressing without magnetic field – isotropic hexaferrites. The application in the LTCC-technology of the method of casting a tape allows obtaining entirely isotropic samples. Development of the technology of low-temperature co-fired ceramics, which consists of alternating ferrites and internal metal electrodes, is relevant in the production of miniature SHF-devices.